Santa goes green - Margaret, Anne.; Chavarri, Elisa (Traverse City, Mich. : Mackinac Island Press, 2008)
A young boy's unusual Christmas request prompts Santa to initiate an energy-saving program at the North Pole.
3.3
K-3
Keywords: Santa Claus -- Juvenile fiction; Christmas -- Juvenile fiction; Green movement -- Juvenile fiction; Environmental protection -- Juvenile fiction; Santa Claus -- Fiction; Christmas -- Fiction; Green movement -- Fiction; Environmental protection -- Fiction; Santa Claus -- Fiction; Christmas -- Fiction; Environmental movement -- Fiction; Environmental protection -- Fiction